Gramsci and Lenin: Hegemony and Philosophy of Praxis - Del Roio, Marcos [UNESP] (My University, 2022)
1937 was a very important year for the Communist International and for the Italian Communist Party. Gramsci’s death had a tremendous impact on Italian communists. The popular front policy demonstrated its limits in the struggle against fascism and fascism, which in turn, consolidated its internal political power and focused on imperial construction. Italy had already occupied Abyssinia and the civil war in Spain continued. Nazi Germany was already preparing to occupy Austria.